Cybersastra Phenomenon as an Implementation of Information and Communication Technology (ICT) in Literary Education - Setyorini, Ririn; Suryanto, Edy; Saddhono, Kundharu; Wulandari, Yosi; Eko Purwanto, Wachid; Riyanto, Sugeng; Fajrin, Rafika; Nugraheni, Luthfa; Sudigdo, Anang; ., Sujarwoko; ., Suprapto; Wardiani, Ririen; et al. (International Journal of Engineering and Technology, 2026)
ICT (Information and Communication Technology) is a facility in which its scope includes all technical devices to process and to deliver all various information. ICT in education is considered as learning based computer and multimedia. ICT utilization as literary work distribution media and its literary learning becomes phenomenal. This results in the easiness of distribution and publication of literary works written by litterateur and the easiness of learning literature wherever and whenever without requiring face-to-face learning. ICT is also very useful for students in searching learning sources related to literature, in terms of literary works like poetry, short story, novel and etc. The easiness of ICT in introducing and distributing literary works stimulates the existences of new litterateur in all rage of age and gender. If litterateur previously was in old age, in this futuristic era the young litterateur can be easily found. This phenomenon, then, contributes in the existence of new term in literature of Cybersastra or literature in virtual world. In this study how ICT role in literature education and how ICT utilization in realizing Cybersastra phenomenon will be discussed.